The impact of coaching communication styles and training programs on novice tennis player satisfaction: A case study from Indonesia - Mohammad Aldi Zakaria; Limpad Nurrachmad (Physical Education and Sports)
Background: The satisfaction of beginner tennis players is often influenced by coaches' communication styles and the structure of training programs.